Does Tourniquet Use in TKA Affect Recovery of Lower Extremity Strength and Function? A Randomized Trial. Issue 1 (January 2016) - Dennis, Douglas A.; Kittelson, Andrew J.; Yang, Charlie C.; Miner, Todd M.; Kim, Raymond H.; Stevens‐Lapsley, Jennifer E.
Abstract: Background: Tourniquet use during total knee arthroplasty (TKA) improves visibility and reduces intraoperative blood loss. However, tourniquet use may also have a negative impact on early recovery of muscle strength and lower extremity function after TKA. Questions/purposes: The purpose of this study was (1) to determine whether tourniquet use affects recovery of quadriceps strength (primary outcome) during the first 3 postoperative months; and (2) to examine the effects of tourniquet application on secondary outcomes: voluntary quadriceps activation, hamstring strength, unilateral limb balance as well as the effect on operative time and blood loss. Methods: Twenty‐eight patients (mean age 62 ± 6 years; 16 men) undergoing same‐day bilateral TKA (56 lower extremities) were enrolled in a prospective, randomized study. Subjects were randomized to receive a tourniquet‐assisted knee arthroplasty on one lower extremity while the contralateral limb underwent knee arthroplasty without extended tourniquet use. In the former group, the tourniquet was inflated just before the incision was made and released after cementation; in the latter group, a tourniquet was not used (10 of 28 [36%]) or inflated only during component cementation (18 of 28 [64%]). The choice of no tourniquet or use just during cementation was based on surgeon choice, because some surgeons felt a tourniquet during cementation was necessary to achieve a dry surgical field to maximize cement fixation. A median parapatellar approach and the identical posterior‐stabilized TKA design were used by all four fellowship‐trained knee surgeons involved. Isometric quadriceps strength, hamstring strength, voluntary quadriceps activation, and unilateral balance were assessed preoperatively, 3 weeks, and 3 months after bilateral knee arthroplasty. Other factors, including pain, range of motion, and lower extremity girth, were assessed for descriptive purposes at each of these time points as well as on the second postoperative day. Results: Quadriceps strength was slightly lower in the tourniquet group compared with the no‐tourniquet group (group difference = 11.27 Nm [95% confidence interval CI, 2.33‐20.20]; p = 0.01), and these differences persisted at 3 months after surgery (group difference = 9.48 Nm [95% CI, 0.43‐18.54]; p = 0.03). Hamstring strength did not differ between groups at any time point nor did measures of quadriceps voluntary activation or measures of unilateral balance ability. There was less estimated intraoperative blood loss in the tourniquet group (84 ± 26 mL) than in the no‐tourniquet group (156 ± 63 mL) (group difference = −74 mL [95% CI, −100 to −49]; p < 0.001). However, there was no difference in total blood loss between the groups (group difference = −136 mL [95% CI, −318 to 45]; p = 0.13). Conclusions: Patients who underwent TKA using a tourniquet had diminished quadriceps strength during the first 3 months after TKA, the clinical significance of which is unclear. Future studies may be warranted to examine the effects of tourniquet use on long‐term strength and functional outcomes. Level of Evidence: Level I, therapeutic study.